A CASE REPORT OF RARE HEPATOSPLENIC T-CELL LYMPHOMA IN AN ADOLESCENT - Jovančić Petković, Danijela; Samardžija, Gordana; Kostić, Gordana; Bogićević, Vesna (Acta medicae Medianae, 2021)
Hepatosplenic T-cell lymphoma is a rare neoplasm that commonly originates from a subset of T lymphocytes expressing γδ T-cell receptors. It is characteristic for young adult men. Clinical presentation usually includes massive enlargement of liver and spleen, typically without involvement of lymph nodes. Bone marrow is often affected in advanced stage of a disease. Clinical course can be progressive and in most cases prognosis is poor.Although splenectomy is not obligatory diagnostic and therapeutic procedure in this case it was a way to establishing diagnosis, accompanied with immunophenotipization of bone marrow cells.  Combination of intensive chemotherapy and allogenic bone marrow transplantation lead to stabile remission.